The Design and Development of an RFID-enabled asset tracking system for challenging environments. (10th December 2007) - Dickman, Peter; McSorley, Gareth P.; Liddell, Jim; Glen, John; , Jim Green
This paper presents an overview of the Phalanx software system from Spartan Solutions. This RFID-based asset-tracking solution exploits robust handheld PDA-based scanners with intermittent-wireless connectivity to integrate operational activities and ERP/logistical information systems for the plant-rental and oil/gas sectors. Unusual challenges in the operating environment and user community have been overcome using novel techniques and unique combinations of technology and methodology. The Phalanx system is an exemplar of an innovative RFID application overcoming significant data management problems. Wireless security issues have been addressed and the system includes internal web-services interfaces that are now being extended for exploitation in operational and corporate oversight applications. The middleware platform enables integration of previously separate applications, extending business processes into the operational domain. The experiences reported in these two case studies have been gained in development, deployment and use in several countries and offer an insight into the effectiveness of an RFID-enabled infrastructure for improved business performance in new and challenging commercial sectors.